A New Generalization of the Lomax Distribution with Increasing, Decreasing, and Constant Failure Rate. (19th July 2017) - Oguntunde, Pelumi E.; Khaleel, Mundher A.; Ahmed, Mohammed T.; Adejumo, Adebowale O.; Odetunmibi, Oluwole A.
Abstract : Developing new compound distributions which are more flexible than the existing distributions have become the new trend in distribution theory. In this present study, the Lomax distribution was extended using the Gompertz family of distribution, its resulting densities and statistical properties were carefully derived, and the method of maximum likelihood estimation was proposed in estimating the model parameters. A simulation study to assess the performance of the parameters of Gompertz Lomax distribution was provided and an application to real life data was provided to assess the potentials of the newly derived distribution. Excerpt from the analysis indicates that the Gompertz Lomax distribution performed better than the Beta Lomax distribution, Weibull Lomax distribution, and Kumaraswamy Lomax distribution.